GROWTH OF GHOST KITCHENS AND VIRTUAL BRANDS - Gagić Jaraković, Snježana; Paunić, Maja; Vujasinović, Vesna; Stanojević, Mateja (The Business of Tourism, 2025)
The hospitality industry is undergoing a profound transformation with the emergence of ghost kitchens and virtual brands, driven by digital innovation and evolving consumer preferences. Ghost kitchens—delivery-only food production facilities—offer cost-effective and scalable solutions for restaurant operators by eliminating the need for physical dining spaces. Similarly, virtual brands leverage data-driven strategies to optimize menu offerings and customer engagement in an increasingly digital marketplace. While these models present significant opportunities, such as market expansion, reduced overhead costs, and operational flexibility, they also pose challenges, including reliance on third-party delivery platforms, brand differentiation, and maintaining food quality. This manuscript examines the growth of ghost kitchens and virtual brands, their economic implications, key operational strategies, and long-term sustainability within the evolving hospitality industry.
Keywords: ghost kitchens; virtual brands; food delivery innovation; hospitality industry transformation